Pengelolaan Digitalisasi Belajar Melalui Literasi Terpadu - Dewi, Erni Ratna; Samudi, Samudi; Hasmirati, Hasmirati; Sujariati, Sujariati; Hartawat, A. Sri Indira i (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2023)
The challenge of integrated literacy is getting more and more complex every year along with the emergence of various technological products. Moreover, there is a technical dimension that will quickly change according to the times. Teachers and other educators have a central role because in the learning process they should provide and allow students to choose various forms of digital media to complete tasks given digital literacy in the curriculum such as ICT introduction material, use of tools to support learning, integrated high literacy computer programming is very useful in the world of education to support implementing a digital-based curriculum that emphasizes students being able to utilize information from various sources of information on the internet for themselves. Students who have the ability to search for information will relieve themselves to learn independently and interact with various information wherever they are.